Successive occurrence of vertebrobasilar dolichectasia induced trigeminal neuralgia, vestibular paroxysmia and hemifacial spasm: A case report. Issue 25 (June 2018) - Han, Jingzhe; Wang, Tingting; Xie, Yanan; Cao, Duanhua; Kang, Zhilei; Song, Xueqin
Abstract: Rationale: Study reported an extremely rare case of trigeminal neuralgia, vestibular paroxysmia, and hemifacial spasm successively occurring in a patient with vertebrobasilar dolichoectasia (VBD). Patient concerns: A 66-year-old female patient presented with episodic vertigo for 20 days before she was admitted to our hospital. Vertigo suddenly occurred when the patient rotated her head 20 days ago, the symptoms of vertigo were improved after continuous 1 to 3 seconds, and similar symptoms were repeated in sleep and rest, with a frequency of 30 to 40 times per day. The patient had a history of hypertension with poor blood pressure control for more than 20 years. Diagnoses: The final diagnosis was vertebrobasilar dolichectasia, right trigeminal neuralgia, and vestibular paroxysmia. Interventions: Vitamin B1 (10 mg), methylcobalamin (0.5 mg), and carbamazepine (0.1 g) were given orally 3 times a day to relieve the symptoms. Outcomes: On the seventh day of drug treatment, the symptoms of paroxysmal vertigo and trigeminal neuralgia were completely relieved, but occasional episodes occurred during the follow-up period. Five months after discharge, right hemifacial spasm appeared in the patient, which did not affect the quality of life of the patient, so the patient did not choose further treatment. Six months after discharge, the patient was lost to follow-up. Lessons: Comprehensive treatment to control VBD risk factors, delay the progression of VBD, and improve clinical symptoms may have a better effect on such patients. However, further research is needed.